2021
DOI: 10.1186/s13244-021-01019-0
|View full text |Cite
|
Sign up to set email alerts
|

CT appearances, patterns of progression, and follow-up of COVID-19: evaluation on thin-section CT

Abstract: Background To retrospectively analyze CT appearances and progression pattern of COVID-19 during hospitalization, and analyze imaging findings of follow-up on thin-section CT. Methods CT findings of 69 patients with COVID-19 were evaluated on initial CT, peak CT, and pre-discharge CT. CT pattern were divided into four types on CT progression. Lesion percentage of pulmonary lobe (lobe score) was graded. Correlation analysis was made between scores an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Then, in the absorption stage, the GGOs and consolidation were gradually absorbed, and fibrotic changes appeared, such as irregular linear opacities and reticular patterns. 6 , 13–15 Fibroplasia is a form of tissue injury and repair that results from the proliferation of fibroblasts, vascular endothelial cells, and connective tissue and finally forms fibrous tissue. 2 Therefore, in the late stages of COVID-19, fibrosis gradually appeared and was gradually absorbed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, in the absorption stage, the GGOs and consolidation were gradually absorbed, and fibrotic changes appeared, such as irregular linear opacities and reticular patterns. 6 , 13–15 Fibroplasia is a form of tissue injury and repair that results from the proliferation of fibroblasts, vascular endothelial cells, and connective tissue and finally forms fibrous tissue. 2 Therefore, in the late stages of COVID-19, fibrosis gradually appeared and was gradually absorbed.…”
Section: Discussionmentioning
confidence: 99%
“… 2–5 Our previous study on a short-term follow-up CT had also demonstrated that the pneumonia had been completely absorbed in 37.7% of 69 COVID-19 patients, and residual pneumonia in 62.3%. 6 The remained CT manifestations included GGO (62.3%), irregular lines (20.8%), reticulation (9.4%), consolidation (3.8%), and pleural thickening adhesion (3.8%). 6 There was one year follow-up study from the onset of symptoms recently, which showed 75% of 209 patients were completely absorbed, and 25% had residual lesions, including reticular patterns (13.4%) and irregular linear opacities (12.0%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the diagnostic performance of CT scans does not depend merely on the prevalence of the disease in the population studied but is also affected by the nonspecific findings of COVID-19 that overlap with those of other conditions, resulting in a substantial rate of false–positive examinations [ 27 ]. Although accumulating data may suggest that a few radiological signs may be considered more specific for COVID-19 pneumonia [ 32 , 33 ], CT appearance is, indeed, not only nonspecific but also time-dependent, displaying predictable spatio–temporal changes [ 34 , 35 ]. Two main reasons could be given for false–negative results: first, symptomatic patients may not show lung abnormalities in the early course of the disease; second, a considerable number of patients with symptomatic upper respiratory tract infections do not develop pneumonia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, at the peak stage (9-13 days), consolidations can be demonstrated. Finally, at the absorption stage (>14 days) a gradual resolution of the findings may be initiated with "fibrous stripes" appearing and the abnormalities frequentlybut not always-resolving at one month and beyond [44,46]. Furthermore, imaging findings on CT can also vary according to the course of the disease at the time of imaging.…”
Section: Ct Imaging Findingsmentioning
confidence: 99%